Review of Community Service Activities with Simple Bookkeeping Objects: Ulasan Kegiatan Pengabdian Masyarakat Dengan Obyek Pembukuan Sederhana - Endah Puspitosarie; Dharmayanti Pri Handini; Alfiana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The small, micro, and medium enterprise (MSME) sector is known to be lacking in recording financial transactions or bookkeeping. Many community service activities have been carried out to provide knowledge, train and assist business people in the form of simple bookkeeping training. The aim of writing this article is to review community service activities with simple bookkeeping objects. The review was carried out by searching online publications for activities over the last 5 years. Search results are arranged in summary form and grouped based on several categories. The results of the review show that the number of activities has tended to increase greatly in the last 3 years. Activity partners are generally MSME actors who are grouped into one training activity. The method that is widely used is providing material and direct practice in financial recording which is done manually. Digitalization of bookkeeping is still minimally communicated to business actors. Further reviews can be carried out to examine digitalization and the level of success/obstacles in its implementation.